PENGARUH RELATIONSHIP MARKETING, E-SERVICE QUALITY DAN HEDONIC SHOPPING MOTIVATION TERHADAP KEPUTUSAN PEMBELIAN DI MARKETPLACE FACEBOOK - Melifia Liantifa; Wahyu Tri Saputra (LP2M Universitas Bina Bangsa, 2024)
This study aims to determine the extend of the influence of Relationship Marketing, E-Service Quality and Hedonic Shopping Motivation on Purchase Decisions on Facebook marketplace both partially and simultaneously. The population in this study were students at STIE Sakti Alam Kerinci. The sample for this study amounted to 90 respondents with the sampling technique convinience. The data Analysis tools used were Likert scale, Multiple Linear Regression Analysis, Partial and Simultaneous Coefficient of determination, t test and f test.Based on the results of the study, conclusions can be drawn, namely the results of research on the influence of Relationship Marketing on Purchase Decisions on the Facebook marketplace can be proven by the value of t calculate variables Relationship Marketing (3.781) > the value of t table (2.00324. The results of research on the effect of e-service quality on Purchase Decisions on Facebook marketplaces can be proven by the t-value of calculating the variables of E-Service Quality (2,480) > the t-value of the table (2,00324) . The results of research on the Effect of Hedonic Shopping Motivation on Purchase Decisions on Facebook marketplaces can be proven by the t-value of calculating the Hedonic Shopping Motivation variable (2,290) > the t-value of the table (2.00324) . The results of the F test were obtained F table with a significant level a = 0.05 and obtained acalculated F value greater than F table as evidenced by the value of Fcount (139.599) > F table (2.769), then Ho was rejected and Ha was accepted from this study it can be concluded that Relationship Marketing, E-Service Quality and Hedonic Shopping Motivation collectively have a positive and significant influence on Purchase Decisions on Facebook marketplaces